Parasitismo por Argulideos (Crustacea: branchiura) em piranhas (Osteichthyes: serrasalminae) e variações limnológicas temporais, baías caiçara – Bacia do Alto Rio Paraguai, Pantanal, Brasil - Fontana, Márcio (2011)
Records of the host-parasite interaction in the tropics are generally restricted to aspects of taxonomic description. The aim of this study was to evaluate and understand the dynamics of ectoparasites by Argulideos (Crustacea: Branchiura) in piranhas (Osteichthyes: Serrasalminae) and list of limnological variables (pH, temperature, dissolved oxygen, depth and water clarity) during a hydrological cicle in the Upper Caiçara Bay (UCB) and Lower Caiçara Bay (LCB), the upper Paraguay River basin, northern Pantanal, Mato Grosso, Brazil. We analyzed 446 specimens of piranhas species Pygocentrus nattereri (Kner, 1858), Serrasalmus maculatus (Kner, 1858) and Serrasalmus marginatus (Valenciennes, 1837), taken between May 2008 and April 2009, the UCB and LCB. The ectoparasites Branchiura found were Dolops bidentata, Dolops longicauda, Dolops sp, Argulus multicolor, Argulus chocomendesi and Dipteropeltis hirundo.The hosts were infested with one or more species of Branchiura. In the three species of piranhas ocurred significant variation in the frequency of ectoparasites fixed between different anatomical sites of the body of host. Pectoral and pelvic fins and peri-opercular region were the sites of fixation with higher frequency of Branchiura, in the three host species. It was recorded prevalence of infestation of 52.6% in P. nattereri, 20.2% in S. maculatus and 15.8% in S. marginatus. In the three host species the level of parasitism by Branchiura varied according to the hydrological cicle for the period of study in two bays. The relative condition factor (Kn) differed significantly between parasitized and not parasitized individuals of P. nattereri and S. maculatus, and the non-infected group had a better body condition factor. In S. marginatus there was no difference between the FC of parasitized and non parasitized. It is the first work involving piranhas and ectoparasites Branchiura in the study area.